2011
DOI: 10.1016/j.labeco.2010.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The distributive and welfare effects of product and labour market deregulation

Abstract: This paper studies the effects of product and labour market deregulation on wage inequality and welfare. By constructing an analytically tractable model in which the level of product market competition and the wages are endogenously distributed among sectors, I show that deregulation in goods market has mixed effects on inequality: the wage variance and the Gini index are lower, but the ratio of the highest over the lowest wage paid in the economy increases. Moreover, deregulation in labour markets raises the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…This is in accordance with empirical evidence that product market liberalization does not deteriorate income inequality(Nicoletti et al, 2001) and that the Gini coefficient falls(Cardullo, 2011). There is also evidence that product market liberalization boosts long-term employment, wages and output (seeOECD, 2001).…”
supporting
confidence: 85%
See 1 more Smart Citation
“…This is in accordance with empirical evidence that product market liberalization does not deteriorate income inequality(Nicoletti et al, 2001) and that the Gini coefficient falls(Cardullo, 2011). There is also evidence that product market liberalization boosts long-term employment, wages and output (seeOECD, 2001).…”
supporting
confidence: 85%
“…Recall also the role of lobbies and interest groups in emphasizing the risks of any reform against the expected benefits (see e.g. Cardullo, 2011). the switch to a more efficient economy with higher output and hence larger tax bases?…”
Section: Second-round Public Financing Implicationsmentioning
confidence: 99%
“…The main findings show that the wage dispersion will decrease when the product price increases, vice versa. Cardullo et al (2011) [14] proposes variance and Gini Coefficient will change in the opposite direction with the competition intensity of product market. In intuition, as the wage gap continues to increase beyond some critical cutoff point, individuals will find it beneficial to rely on sabotage against their rivals eventually since effort is getting too "expensive" to use.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, E 1 E 2 is the employment opportunity loss of economic entity C 1 resulting from regulation, compared with economic entity C 2 . Cardullo [11] studied the effects of product and labor market deregulation on wage inequality and welfare, and showed that deregulation of goods market has mixed effects on inequality: the wage variance and the Gini index are lower, but the ratio of the highest over the lowest wage paid in the economy increases.…”
Section: Regulation and Employment Opportunity Lossmentioning
confidence: 99%